The Long-term Photometric Behavior of 39 Semiregular Variable Stars - Cadmus, Robert R. (The Astronomical journal, 2024)
Photometric measurements of the light and color variations of 39 semiregular variable stars over a 30 yr time interval have been used to explore the systematics of these variations. These results show the complex nature of the frequency compositions of the light curves of these stars. The frequencies present in the light curves tend to be harmonic in nature, suggesting that both modes of pulsation and shape effects may be involved and the nature of the variations indicates that stochastic excitation is involved.